Functional analysis of depression associated proteins: role of TRK, BDNF, CYP2B6, POLG, PICK1 Biomarkers for early detection and treatment of depression - Jurashe, Partha Sanjana (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.